Oxalic Acid Enabled Emission Enhancement and Continuous Extraction of Chloride from Cesium Lead Chloride/Bromide Perovskite Nanocrystals. Issue 34 (5th July 2019) - Wang, Shixun; Shen, Xinyu; Zhang, Yu; Zhuang, Xingwei; Xue, Dingke; Zhang, Xiangtong; Wu, Jinlei; Zhu, Jinyang; Shi, Zhifeng; Kershaw, Stephen V.; Yu, William W.; Rogach, Andrey L.
Abstract: All‐inorganic cesium lead halide perovskite nanocrystals (NCs) have demonstrated excellent optical properties and an encouraging potential for optoelectronic applications; however, mixed‐halide perovskites, especially CsPb(Cl/Br)3 NCs, still show lower photoluminescence quantum yields (PL QY) than the corresponding single‐halide materials. Herein, anhydrous oxalic acid is used to post‐treat CsPb(Cl/Br)3 NCs in order to initially remove surface defects and halide vacancies, and thus, to improve their PL QY from 11% to 89% for the emission of 451 nm. Furthermore, due to the continuous chelating reaction with the oxalate ion, chloride anions from the mixed‐halide CsPb(Cl/Br)3 perovskite NCs could be extracted, and green emitting CsPbBr3 NCs with PL QY of 85% at 511 nm emission are obtained. Besides being useful to improve the emission of CsPb(Cl/Br)3 NCs, the oxalic acid treatment strategy introduced here provides a further tool to adjust the distribution of halide anions in mixed‐halide perovskites without using any halide additives. Abstract : Unlike conventional passivating strategies, oxalic acid could directly remove the surface defects and vacancies of cesium lead chloride/bromide perovskite nanocrystals to boost their blue emission with photoluminescence quantum yields (PL QY) of 89% at 451 nm and would gradually shift the emission to the pure green with PL QY of 85% at 511 nm under continuous chelating actions.